2019
DOI: 10.3390/rs11060677
|View full text |Cite
|
Sign up to set email alerts
|

Improving an Extreme Rainfall Detection System with GPM IMERG data

Abstract: Many studies have shown a growing trend in terms of frequency and severity of extreme events. As never before, having tools capable to monitor the amount of rain that reaches the Earth’s surface has become a key point for the identification of areas potentially affected by floods. In order to guarantee an almost global spatial coverage, NASA Global Precipitation Measurement (GPM) IMERG products proved to be the most appropriate source of information for precipitation retrievement by satellite. This study is ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 15 publications
4
48
0
2
Order By: Relevance
“…floods). This has been extensively discussed in previous research (Hollmann et al, 2013a;Mazzoglio et al, 2019) Technical comments 16. Comment: Sentence in line 128 requires revision.…”
Section: Interactive Commentmentioning
confidence: 74%
“…floods). This has been extensively discussed in previous research (Hollmann et al, 2013a;Mazzoglio et al, 2019) Technical comments 16. Comment: Sentence in line 128 requires revision.…”
Section: Interactive Commentmentioning
confidence: 74%
“…Then the interpolated precipitation at each station was In this study, the evaluations were conducted in three steps. In the first step, the performance of the three NWP models and SPEs in terms of capturing the spatial distribution of precipitation for the three flood events (17)(18)(19)(20)(21)(22)(24)(25)(26) March, and 31 March to 2 April 2019, respectively) were compared. The numerical forecast and SPE data have a 50 × 50 km and~10 × 10 km spatial resolution, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Sunikumar et al demonstrated the ability of IMERG to follow the intraseasonal variability with minor differences observed in the maximum values of precipitation during the rainy season over Japan, Philippines, and Nepal [25]. Mazzoglio et al improved an extreme precipitation detection system using IMERG data and stated that this product guarantees good results when the precipitation aggregation interval is equal to or greater than 12 h [26]. However, no comparison has been made so far between the ensemble forecasts with IMERG product for extreme flood events over Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of the accuracy in representing extreme rainfall events for varying time aggregation intervals is one more problem. A study of Mazzoglio et al [241] concluded that satellite precipitation data guarantee good results when the rainfall aggregation interval is ≥12 h; a 24-h aggregation interval ensures a probability of detection >80%. At the same time, the results depend on the adopted spatial domain and require a multiscale approach to regional trend analysis [242].…”
Section: Observing Extremesmentioning
confidence: 99%